PROSPEK PENGEMBANGAN KOMODITAS SUMBER KARBOHIDRAT KAYA ANTOSIANIN MENDUKUNG DIVERSIFIKASI PANGAN FUNGSIONAL / Prospects of Anthocyanin-Rich Carbohydrates Sources Commodity Development to Support Functional Food Diversification - Suarni suarni; Muh. Aqil; Muh. Azrai (Jurnal Penelitian dan Pengembangan Pertanian, 2020)
One of the sources of functional foodstuff is carbohydrate-based commodities which contain anthocyanin. These commodities include black rice, purple corn, and purple sweet potato. The anthocyanin compound is a pigment which is responsible for the purple color to the produced commodities. This compound possesses antioxidative activities which are able to bind with free radical compounds and protect human body against various diseases.Physiological function of the anthocyanin in foodstuff has attract particular interest for further exploration, particularly on its bioavailability nature, functional food ingredients, and its product’s appearances. Several anthocyanin-rich varieties such as Jeliteng black rice, Srikandi Ungu corn, and Antin purple sweet potato has been released by Indonesian Agency for Agricultural Research and Development (IAARD). In the future, development of processed functional food product is expected to raise in line with the increase in the public’s interest on the important of the health. The specific function of antioxidant derived from the anthocyanin compound enable human immunity increase which is recently getting popular, particularly during Covid-19 pandemic. Potential development of the foodstuffs associated with anthocyanin involves various research from upstream to downstream, starting from superior varieties development which contain higher anthocyanin content, by product creation with higher functional values and preferred by the consumers.Keywords: Carbohydrates, anthocyanin, functional food, diversification. AbstrakSalah satu sumber bahan pangan fungsional adalah komoditas berbasis karbohidrat dan mengandung antosianin. Komoditas tersebut antara lain padi beras hitam, jagung ungu, dan ubi jalar ungu. Senyawa antosianin merupakan pigmen yang memberikan warna ungu pada produk yang dihasilkan. Antosianin memiliki aktivitas antioksidan, yang mampu mengikat senyawa radikal dan melindungi tubuh dari penyakit. Fungsi fisiologis dari antosianin dalam bahan pangan telah menarik perhatian untuk dilakukan eksplorasi sifat bioavailability, fungsi pangan fungsional, dan tampilan produknya. Beberapa varietas unggul komoditas sumber karbohidrat kaya antosianin seperti padi hitam Jeliteng, jagung Srikandi Ungu, dan ubi jalar ungu Antin telah dilepas oleh Balitbangtan. Ke depan, pengembangan produk olahan pangan fungsional diharapkan semakin meningkat seiring dengan meningkatnya perhatian masyarakat akan pentingnya kesehatan. Fungsi khusus antioksidan dari senyawa antosianin dapat menaikkan imun tubuh yang sangat dibutuhkan masyarakat, apalagi dalam masa pandemi Covid-19. Potensi pengembangan bahan pangan berantosianin memerlukan penelitian dari hulu hingga hilir, mulai dari perakitan varietas unggul mengandung antosianin lebih tinggi sampai teknologi pengolahan untuk menghasilkan produk olahan yang lebih berkualitas, dengan sifat fungsional yang lebih tinggi, dan disenangi oleh konsumen.Kata kunci: Karbohidrat, antosianin, pangan fungsional, diversifikasi.